Application of the Topsis Method in Selecting the Best Laying Chicken Feed - Lanni Putri Nami; Muhammad Ikhlas; Radius Prawiro (Universitas Putra Indonesia YPTK Padang, 2023)
A person's limited ability in a particular field makes them think hard about getting a job that can fulfill their daily needs. Now many people are starting to try to switch to the world of animal husbandry. One of them is raising chickens to take their eggs. Choosing good laying hen feed is a very important main factor, especially for consumption by laying hens. Therefore, a decision support system was designed in selecting the best laying hen feed using the Techinique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The TOPSIS method is an approach that determines solutions based on the closest distance from the positive ideal solution and the furthest distance from the negative ideal solution in order to obtain the optimal alternative. The result achieved is that the system is able to show which laying hen feed has the best quality which will become laying hen feed for laying hen breeders based on predetermined criteria so that Sinar Animal Husbandry can easily determine the best laying hen feed . The results of calculations using the Topsis method showed that alternative A3, namely HI-PRO-VITE 124, had the highest value with an alternative value of 0.6568